Genetic consequences of population expansions and contractions in the common hippopotamus (Hippopotamus amphibius) since the Late Pleistocene. Issue 10 (22nd April 2015) - Stoffel, Céline; Dufresnes, Christophe; Okello, John B. A.; Noirard, Christian; Joly, Pierre; Nyakaana, Silvester; Muwanika, Vincent B.; Alcala, Nicolas; Vuilleumier, Séverine; Siegismund, Hans R.; Fumagalli, Luca
Abstract: Over the past two decades, an increasing amount of phylogeographic work has substantially improved our understanding of African biogeography, in particular the role played by Pleistocene pluvial–drought cycles on terrestrial vertebrates. However, still little is known on the evolutionary history of semi‐aquatic animals, which faced tremendous challenges imposed by unpredictable availability of water resources. In this study, we investigate the Late Pleistocene history of the common hippopotamus ( Hippopotamus amphibius ), using mitochondrial and nuclear DNA sequence variation and range‐wide sampling. We documented a global demographic and spatial expansion approximately 0.1–0.3 Myr ago, most likely associated with an episode of massive drainage overflow. These events presumably enabled a historical continent‐wide gene flow among hippopotamus populations, and hence, no clear continental‐scale genetic structuring remains. Nevertheless, present‐day hippopotamus populations are genetically disconnected, probably as a result of the mid‐Holocene aridification and contemporary anthropogenic pressures. This unique pattern contrasts with the biogeographic paradigms established for savannah‐adapted ungulate mammals and should be further investigated in other water‐associated taxa. Our study has important consequences for the conservation of the hippo, an emblematic but threatened species that requires specific protection to curtail its long‐term decline.